Tiny Drosophila makes giant strides in cancer research. - Yamamura, R.; Ooshio, T.; Sonoshita, M. (Cancer Science, 2021)
Cancer burden has been increasing worldwide, making cancer the second leading cause of death in the world. Over the past decades, various experimental models have provided important insights into the nature of cancer. Among them, the fruit fly Drosophila as a whole-animal toolkit has made a decisive contribution to our understanding of fundamental mechanisms of cancer development including loss of cell polarity. In recent years, scalable Drosophila platforms have proven useful also in developing anti-cancer regimens that are effective not only in mammalian models but also in patients. Here, we review studies using Drosophila as a tool to advance cancer study by complementing other traditional research systems.